2020
DOI: 10.3390/biom10030425
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis and Characterization of Zinc Oxide Nanoparticles Using Eucalyptus globules and Their Fungicidal Ability Against Pathogenic Fungi of Apple Orchards

Abstract: Eucalyptus globules belonging to the Myrtaceae family was explored for the synthesis of zinc oxide nanoparticles and for biological applications. The aqueous extract of the synthesized zinc nanoparticles (ZnNPs) was characterized using UV-visible spectrophotometer, FTIR, SEM and TEM. The aqueous broth was observed to be an efficient reducing agent, leading to the rapid formation of ZnNPs of varied shapes with sizes ranging between 52–70 nm. In addition, antifungal activity of the biosynthesized ZnNPs was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(40 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…The ever-increasing problem of antibiotic resistance in pathogenic microorganisms challenges the research community to develop cost-effective processes for synthesizing novel antimicrobial agents [ 10 ]. Silver NPs cause the destruction of microorganisms by attacking and damaging their negatively charged cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-increasing problem of antibiotic resistance in pathogenic microorganisms challenges the research community to develop cost-effective processes for synthesizing novel antimicrobial agents [ 10 ]. Silver NPs cause the destruction of microorganisms by attacking and damaging their negatively charged cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus has been used for medicine, ornament purposes, cosmetics, food, and the pulp industry since ancient times. Some constituents extracted from eucalyptus leaf illustrated antimicrobial and anti-inflammatory activities including (1, 8-cineole eucalyptol) ( Vecchio et al, 2016 ), a-Pinene, 8-Pinene, Sabinene ( Dellacassa et al, 1990 ), ZnO ( Ahmad et al, 2020 ), FeO 2 , and Ag ( Salgado et al, 2019 ). This study revealed that eucalyptus leaf extract showed antimicrobial activity against E. coli causing colibacillosis disease in poultry.…”
Section: Discussionmentioning
confidence: 99%
“…( Wang et al, 2017 , Zulfiqar et al, 2019 ). We synthesized ZnO-NPs from eucalyptus leaves by using ZnO salt ( Ahmad et al, 2020 ). The environmentally friendly green synthesis of ZnO-NPs with eucalyptus is a safe, non-toxic, low-cost process.…”
Section: Discussionmentioning
confidence: 99%
“…An excess of over 70% of 1,8-cineole in Eucalyptus makes it suitable as a pest repellent. For example, Indian E. globulus essential oils are targeted for medicinal purposes due to their activity against bacteria, fungi, and oxidative agents [ 72 ]. Additionally, Eucalyptus oils are useable in food additives, fragrances, and pharmaceutical products [ 73 ].…”
Section: Eucalyptus In a General Viewmentioning
confidence: 99%
“…Eucalyptus parts are collected, followed by rinsing and drying several times, then the dried materials are powdered and added to deionized water. The resultant extract was then centrifuged for a few minutes and filtered to obtain the final volume [ 72 ]. According to Chand et al [ 39 ], the second step of synthesis is carried out by adding a relevant metal salt solution to the extract, keeping it at a certain temperature for a specific time until the color of the solution changes, which is an evidence of the reduction of the metal ion and NP formation.…”
Section: Synthesis Of Mnps From Eucalyptusmentioning
confidence: 99%